Ektoparasit Cacing pada Benih Ikan Nila (Oreochromis niloticus) di Balai Benih Ikan Pandak dan Sidabowa Kabupaten Banyum - Mulia, Dini Siswani; Mahdiana, Arif; Utami, Rakhmawati (Sain Akuatik, 2006)
The aims of this research were to know the type of helminth ectoparasites and prevalency of helminth ectoparasites in fish fry of nila (Oreochromis niloticus). Experiments held at two  different ponds, Local Hatchery Center Pandak Sidabowa, Banyumas Regency. The research used survey method. The location of site was determined with purposive sampling method. The samples were taken randomly (random sampling) from two locations. Total fishes samples were 135, as follow 75 of fishes from Pandak and other 60 fishes from Sidabowa, with twice replication of taking samples.  The data were analyzed descriptively and continued analyzed by t test to compare the prevalency of ectoparasites in Pandak and Sidabowa. The result of this research showed that nila fish fry at the Pandak and Sidabowa, were found two kinds of helminth parasites such as Dactylogyrus sp. and  Gyrodactylus sp.  Higher prevalency occurred on the body surface of nila fish fry that caused by Gyrodactylus sp., 76% in Pandak and 80% in Sidabowa. While on the infected to gills of nila fish fry that caused by Dactylogyrus sp., 45,33% in Pandak and 48,33% in Sidabowa.